ISIM MAUSHUL PADA AYAT-AYAT MUNAKAHAT KAJIAN SINTAKSIS DAN SEMANTIK - Imron Gozali (Islamic Family Law, STAI Sangatta Kutai Timur, 2023)
This study aims to describe the types of isim mausul, shilah mausul, position, and contextual meaning in munakahat verses in the Koran. This research is included in library research or Library Research with a qualitative descriptive approach. The results of this study found that there are two forms of isim maushul, namely isim maushul khaash and isim maushul musytarak. From the shilah there are shilah in the form of several fi'iliah, namely fi'il madhi, fi'il mudhori, and shibih sum, namely jer majrur. While from a'id found dhomir mustatir and dhomir bariz. In his position, isim maaushul has the position of khobar muqoddam, mudhof ilaif, majrur, mubatada' maful bih, badal and in terms of its meaning, it is found the meaning of people who, something that is, material that is, what is that, oaths that are, food that is and women that are.